Comparative outcomes of image-guided percutaneous catheterization versus direct visualization catheterization for peritoneal dialysis: A meta-analysis - Yi Li; Lifang Li; Meiju Wei; Yanxiong Qin; Yuechen Qin; Yue Zou; Haijian Zeng; Chunlan Li; Tingting Liao (PLoS ONE, 2025)
Introduction Debate persists on the optimal catheterization method for peritoneal dialysis (PD). This meta-analysis aimed to compare the outcomes of image-guided percutaneous catheterization (IGPC) versus direct visualization catheterization (DVC) for peritoneal dialysis. Materials and methods From the inception of the database until July 16, 2024, four databases (Medline, Embase, Web of Science, and the central database) were searched for literature comparing IGPC versus DVC for peritoneal dialysis. Meta-analyses were conducted on infectious complications, mechanical complications, one-year PD catheter survival, and catheter removal rates. Results Totally 11 studies were included in this meta-analysis, comprising a total of 8,981 patients, of which 2,518 patients received IGPC and 6,463 patients received DVC. IGPC exhibited lower rates of infection complications (OR = 0.73, 95% CI: 0.54-0.99, P = 0.04) mechanical complications (OR = 0.64, 95% CI: 0.42-0.99, P = 0.04) and catheter removal compared to DVC (OR = 0.63, 95% CI: 0.50-0.78, P < 0.0001). However, there was no significant difference in one-year PD catheter survival between the two groups (OR = 1.33, 95% CI: 0.78-2.27, P = 0.30). Conclusions This meta-analysis concluded that IGPC was a safe and effective catheterization method for PD. The results demonstrated that IGPC significantly reduced the incidence of infection complications, mechanical complications, and catheter removal compared to DVC. No notable disparity in one-year PD survival was detected between the two groups. Trial registration PROSPERO (CRD42024606795).